Digital Marketing Strategy for Indonesia Health Services: A Scoping Review - Arizka, Ulfa Dwi; Wijaya, ⁠Andriana Putri; Ernawaty, Ernawaty (Griya Eka Sejahtera, 2025)
Background: Digital marketing is a strategic approach that seeks to enhance market dominance by utilizing digital technology platforms like social media and mobile applications. Hence, it is vital to devise and execute a well-defined strategy in order to cultivate an effective marketing plan for health services.Methods: This article employs a scoping review and the references were selected based on Preferred Reporting Items for Systematic Reviews (PISMA-ScR) criteria between 2020 and 2024 using searches conducted on Scopus, PubMed, Science Direct, Researchgate, and Google Scholar. Total of 254 articles, six article fulfilled the criteria for inclusion.Results: The references including articles between 2020 and 2024 using searches conducted on Scopus, PubMed, Science Direct, Researchgate, and Google Scholar. Total of 254 articles, six article fulfilled the criteria for inclusion.Conclusion: This article show that digital marketing has many strategies depend on the need of health services. There are a number of different approaches that can be utilized, such as the SMART approach, Kotler's 5A theory, and the IDEA method. Health services also understand and analysis of the surrounding environment, gaining an understanding of the online behavior of the target audience, and ensuring that a positive attitude is maintained in both online and offline interactions.